Quantification of 4-hydroxyisoleucine content in treated and untreated Fenugreek seeds using GC - MR Haeri; MR Shams-Ardakani; M Rahbani; M Izaddust; M Khanavi (Institue of Medicinal Plants, ACECR, 2010)
Background: There are some reports regarding antidiabetic activity of 4-hydroxyisoleucine, however its hypoglycemic property must be proven completely before presentating as a new drug. Preparing suitable amount of 4-hydroxyisoleucine is nesessary for supporting in vivo studies. Objective: The purpose of the present study was isolation of 4-hydroxyisoleucine, comparing 4-hydroxyisoleucine content in two samples of Fenugreek seeds collected form two distinct parts of Iran and finally the effect of germination and supplementation by isoleucine on 4-hydroxyisoleucine yield. Methods: 4-hydroxyisoleucine was successfully isolated passing seed amino acid extract through ion exchange and silica gel column and then crystallization on methanol. 4-hydroxyisoleucine content in various samples was assessed by GC. Results: Seeds from Northwestern of Iran had higher amount of 4-hydroxyisoleucine in comparison to Central Iran. Furthermore yields from germinating seeds were 2 folds higher than the dried seeds, and could be increased 6 fold by inclusion of isoleucine supplement in the irrigation water. Conclusion: simple procedures can be engaged for improving yields of 4-hydroxyisoleucine isolated from fenugreek up to six-fold by using of germinated seeds supplemented with isoleucine.